FENOMENA MENINGKATNYA KEHAMILAN DI LUAR NIKAH AKIBAT BELIS DI KOTA MBAY KECAMATAN AESESA KABUPATEN NAGEKEO PROVINSI NUSA TENGGARA TIMUR - Yusril Mandar; Ahmad Subekti; Humaidi Humaidi (Prodi Ahwal syakhshiyyah Fakultas Agama Islam UNISMA, 2022)
In Mbay Flores, East Nusa Tenggara (NTT) province, the dowry or what they call it belis is very high. Belis is calculated so expensive, the range of dowry that must be prepared by the groom from 80 million to 120 million, depending on educational background and social status. And this makes the people (youth) in Mbay object to the large and expensive burden of buying and selling. This causes a lot of marriages outside of marriage. Between dowry or what they call belis is closely related to the systematic life of society. This means that if there is no belis, it means that there is no marriage. Belis, or commonly known as a dowry at weddings in other cities in Indonesia, is usually given the equivalent but not so in the Mbay Flores community, East Nusa Tenggara. Belis, which is also stated as a dowry, the amount exceeds the usual dowry. In the Mbay Flores community, the dowry or belis is sometimes even in the form of their livestock such as cows or buffalo and the most important thing is the Mbay traditional cloth